2010
DOI: 10.1007/s12275-010-9193-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cultivated fungi isolated from grape marc wastes through the use of amplified rDNA restriction analysis and sequencing

Abstract: Microbial assessment of grape marc wastes, the residual solid by-product of the wine-industry, was performed by identifying phylogenetically the fungal culturable diversity in order to evaluate environmental and disposal safety issues and to discuss ecological considerations of applications on agricultural land. Fungal spores in grape marc were estimated to 4.7 x 10(6) per g dry weight. Fifty six fungal isolates were classified into eight operational taxonomic units (OTUs) following amplified ribosomal DNA res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…Aliquot (100 μ L) of each transformation was spread on LB/ampicillin/IPTG/X-gal plates and incubated at 37°C for 16 h. For each sample, 192 white colonies were picked out, which were amplified by 27f and 1492r primer that the positive clones were confirmed through. Then, 10 μ L target insert fragments (about 1,500 bp) were digested by 3 U restriction endonuclease Hinf I (TaKaRa) [ 13 , 14 ] and Pst I (TaKaRa) [ 15 ] at 37°C for 2 h. Clones having the same restriction patterns were defined as an operational taxonomic unit (OTU).…”
Section: Methodsmentioning
confidence: 99%
“…Aliquot (100 μ L) of each transformation was spread on LB/ampicillin/IPTG/X-gal plates and incubated at 37°C for 16 h. For each sample, 192 white colonies were picked out, which were amplified by 27f and 1492r primer that the positive clones were confirmed through. Then, 10 μ L target insert fragments (about 1,500 bp) were digested by 3 U restriction endonuclease Hinf I (TaKaRa) [ 13 , 14 ] and Pst I (TaKaRa) [ 15 ] at 37°C for 2 h. Clones having the same restriction patterns were defined as an operational taxonomic unit (OTU).…”
Section: Methodsmentioning
confidence: 99%
“…Abe et al (2010) have described the presence of T. mycotoxinivorans in fresh shavings of palm tissue that were damaged by beetle larvae (Coleoptera: Dryophthoridae) in Japan. It occurrence was also described in grape marc in southern Peloponnese, Greece, by Ntougias et al (2010), which reports it as closely related to an unidentified member of Trichosporon clade, isolated from the xylophagous beetle Phrenapetes bennetti (Tenebrionidae), collected in Panama by Suh et al (2005). Hickey et al (2009) have found T. mycotoxinivorans to be a novel respiratory pathogen in patients with cystic fibrosis.…”
Section: Resultsmentioning
confidence: 94%